Pembuatan Pestisida Nabati Daun Mimba Untuk Mengendalikan Hama Pada Tanaman Di Desa Rumpet Kecamatan Krueng Barona Jaya Kabupaten Aceh Besar - Arif Sardi; Putri Magfirah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This activities aim to provide understanding and skills to the community in Rumpet Village, Krueng Barona Jaya Subdistrict, Aceh Besar Regency, on utilizing local resources to naturally control plant pests. The primary focus of this activity is the process of making botanical pesticides from neem leaves as an environmentally friendly solution to sustain agriculture in the region. The activity begins with a socialization on the importance of sustainable pest control and the adverse effects of chemical pesticides. It involves active participation from the community in collecting and identifying neem leaves as the main ingredient. The process of extracting active compounds from neem leaves is also taught to the community, along with formulation techniques and the application of the resulting botanical pesticide. The outcomes of this activity include an increase in community knowledge about natural plant pest control and their empowerment in producing and using botanical pesticides from neem leaves. This community service is expected to make a positive contribution in promoting sustainable and resilient farming practices in Rumpet Village, inspiring surrounding communities to adopt similar approaches in their agricultural management.